Cortical and Subcortical Alterations in Medication Overuse Headache - Mehnert, Jan; Hebestreit, Julia; May, Arne (Frontiers in Neurology, 2018)
Medication-overuse headache is an increasing problem in headache clinics and therapy includes drug withdrawal. Although it has been shown that the orbitofrontal cortex is hypo-metabolic and exhibits less gray matter in these patients the functional role of this finding is still unclear as virtually no functional imaging studies exploring withdrawal of medication have been published. We compared structural and functional magnetic resonance images of 18 patients before and after drug withdrawal with age and gender matched controls using a well-established nociceptive f-MRI paradigm. We reproduced structural changes in the orbitofrontal cortex of the patients which highly correlated with the clinical outcome of medication withdrawal. The neuronal activity before drug withdrawal in pain related regions (operculum, insula, spinal trigeminal nucleus) was reduced compared to after drug withdrawal and the orbitofrontal cortex showed a reduced functional connectivity to the nociceptive input region (spinal trigeminal nucleus) and the cerebellum which regained after withdrawal. These data suggest the seminal role of the orbitofrontal cortex as a mediator between bottom-up and top-down stream in headache processing.